Interdisciplinary Health Care Professionals' Perceptions of the Causes and Consequences of the Opioid Crisis: Developing Rural Community Partnerships to Increase Access to Naloxone - Laura C. Palombi; Stephany Medina; Kelsey Ronayne; Ashley Dahly; Heather Blue (The University of Alabama, 2022)
Opioid overdoses kill thousands of people each year, and overdose rates continue to increase. Community-university partnerships are desperately needed to provide the multipronged and multiagency responses demanded by the opioid crisis. In this study, community and university partners used a consensual qualitative research approach to analyze survey results from continuing medical education sessions in rural communities. The health care providers surveyed had variable attitudes toward the opioid crisis, ranging from empathy for patients' situations to denial that an opioid crisis exists. The voices of these professionals are critical to community partners' ongoing work to address the opioid crisis. Data from this study supported the formulation of subsequent programming for health care professionals and community members as well as the launch of fruitful opioid-focused partnerships. Understanding health care professionals' perceptions of the opioid crisis will allow public health and university teams to provide effective interventions in opioid prescription, naloxone distribution, and stigma reduction to ultimately lessen opioid dependency and overdose.